Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 1:
\(f(x)=ax^2+bx+c\Rightarrow \left\{\begin{matrix} f(-2)=a(-2)^2+b(-2)+c=4a-2b+c\\ f(3)=a.3^2+b.3+c=9a+3b+c\end{matrix}\right.\)
\(\Rightarrow f(-2)+f(3)=(4a-2b+c)+(9a+3b+c)\)
\(=13a+b+2c=0\)
\(\Rightarrow f(-2)=-f(3)\Rightarrow f(-2)f(3)=-f(3)^2\leq 0\) do \(f(3)^2\geq 0\)
Ta có đpcm.
Bài 2:
Thay $x=-3$ ta có:
\(f(-3)=a.(-3)+5=-2\)
\(\Rightarrow a=\frac{7}{3}\)
Vậy $a=\frac{7}{3}$
![](https://rs.olm.vn/images/avt/0.png?1311)
\(1,\text{Ta có: với a=1;b=-6;c=11 thì }P\left(x\right)=x^2-6x+11=\left(x-3\right)^2+2>0\Rightarrow\text{vô nghiệm}\)
\(2,\text{ với: x=3}\Rightarrow f\left(3\right)+5f\left(\frac{1}{3}\right)=27\)
\(với:x=\frac{1}{3}\text{ thì:}f\left(\frac{1}{3}\right)+5f\left(3\right)=\frac{1}{27}\)
\(\Rightarrow6\left(f\left(3\right)+f\left(\frac{1}{3}\right)\right)=\frac{730}{27}\Leftrightarrow f\left(3\right)+f\left(\frac{1}{3}\right)=\frac{365}{81}\Rightarrow4f\left(3\right)=\frac{-362}{81}\Rightarrow f\left(3\right)=\frac{-362}{324}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 1:
a) Ta có: \(P\left(x\right)=3x^4+2x^2-3x^4-2x^2+2x-5\)
\(=\left(3x^4-3x^4\right)+\left(2x^2-2x^2\right)+2x-5\)
\(=2x-5\)
Bài 1:
b)
\(P\left(-1\right)=2\cdot\left(-1\right)-5=-2-5=-7\)
\(P\left(3\right)=2\cdot3-5=6-5=1\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a,f\left(x\right)+g\left(x\right)=5x^2-2x+5+5x^2-6x-\dfrac{1}{3}\\ =10x^2-8x+\dfrac{14}{3}\\ b,f\left(x\right)-g\left(x\right)=5x^2-2x+5-5x^2+6x+\dfrac{1}{3}\\ =4x+\dfrac{16}{3}\\ c,f\left(x\right)-g\left(x\right)=4x+\dfrac{16}{3}=0\\ \Leftrightarrow4x=-\dfrac{16}{3}\Leftrightarrow x=-\dfrac{4}{3}\)